Makna Tari Kontemporer Barangan Karya Otniel Tasman: Suatu Tinjauan Semiotika Tari - Fresti Yuliza (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2022)
This article discusses a contemporary dance work entitled Barangan, which was composed by Otniel Tasman, an Indonesian contemporary dance choreographer from Banyumas based in Surakarta. The aim is to reveal the meaning of the Barangan choreography in relation to the Lengger, a traditional Bayumas dance. The research was conducted by applying qualitative research methods with descriptive analysis methods based on the theoretical framework of dance semiotics. Research shows that the contemporary Barangan dance is a metaphor that represents the wider panorama of Banyumas culture. Seen in this way, the lengger in the Barangan choreography is a kind of metonymy of the minor folk arts, which is always confronted with the arts of the city or the arts of the dignitaries and aristocrats. When it was adopted as a contemporary dance piece in Barangan, the Legger dance was transformed into a kind of symbol of resistance and struggle.Keyword: Contemporary Dance; Barangan; Othniel Tasman; Lengger; Dance SemioticAbstrakArtikel ini membahas tentang karya tari kontemporer berjudul Barangan, yang disusun oleh Otniel Tasman, salah seorang koreografer tari kontemporer Indonesia asal Banyumas yang berbasis di Surakarta. Tujuannya adalah untuk mengungkapkan makna dari karya koreografi Barangan tersebut dalam kaitannya dengan lengger, sebuah tari tradisional Bayumas. Penelitian dilakukan dengan menerapkan metode penelitian kualitatif dengan metode analisis deskriptif yang berpijak pada kerangka teoretik semiotika tari. Penelitian menunjukkan bahwa tari kontemporer Barangan adalah metafora yang mewakili panorama kebudayaan Banyumas secara luas. Dilihat dengan cara ini, maka lengger dalam koreografi Barangan adalah semacam metonimi dari kesenian rakyat kecil, yang senantiasa berhadapan dengan kesenian kota atau kesenian para pembesar dan bangsawan. Ketika diangkat menjadi karya seni kontemporer Barangan, tari lengger bertransformasi menjadi semacam simbolisasi perlawanan dan perjuangan.Kata kunci: Tari Kontemporer; Barangan; Otniel Tasman; Lengger; Semiotika Tari